RANCANG BANGUN E-INVENTORY SPARE PART KAPAL BERBASIS CODEIGNITER PADA PT PELAYARAN NASIONAL SANDICO OCEAN LINE BATAM - Lindo, Junius; Tukino, Tukino (Universitas Putera Batam, 2023)
With the rapid advancement of information technology, computers have become highly useful devices for humans in various fields. In the context of companies, an inventory system is needed to ensure smooth operational activities. Inventory encompasses a complete list of items owned by an office, institution, factory, or company, and is used to carry out specific tasks. PT Pelayaran Nasional Sandico Ocean Line Batam is one company that still uses a manual or conventional inventory system to record ship spare parts inventory. Therefore, a web-based information system is proposed to replace the existing system. In the development of this website, the PHP programming language is used to create dynamic and interactive web pages. For the framework, Codeigniter is chosen based on the previously explained concepts. Codeigniter is selected as one of the best frameworks for building web applications because it provides various tools that aid in faster development, a stable structure, and ease of maintenance. The development of this Codeigniter-based website aims to assist developers in efficiently building web applications. By using Codeigniter, developers can easily handle complex PHP code, seamlessly integrate components, and achieve useful functionality with simple configuration.